2010
DOI: 10.1016/j.antiviral.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Compounds that target host cell proteins prevent varicella-zoster virus replication in culture, ex vivo, and in SCID-Hu mice

Abstract: Varicella-zoster virus (VZV) replicates in quiescent T cells, neurons, and skin cells. In cultured fibroblasts (HFFs), VZV induces host cyclin expression and cyclin-dependent kinase (CDK) activity without causing cell cycle progression. CDK1/cyclin B1 phosphorylates the major viral transactivator, and the CDK inhibitor roscovitine prevents VZV mRNA transcription. We investigated the antiviral effects of additional compounds that target CDKs or other cell cycle enzymes in culture, ex vivo, and in vivo. Cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 61 publications
0
35
1
Order By: Relevance
“…We found that regulation of the cell cycle by VZV ORF12 protein was dependent on PI3K, which supports this hypothesis. This is further bolstered by observations that the inhibition of intracellular signaling pathways (34,35) or cell cycle regulators (51,52) by small molecules reduces VZV replication.…”
Section: Discussionmentioning
confidence: 99%
“…We found that regulation of the cell cycle by VZV ORF12 protein was dependent on PI3K, which supports this hypothesis. This is further bolstered by observations that the inhibition of intracellular signaling pathways (34,35) or cell cycle regulators (51,52) by small molecules reduces VZV replication.…”
Section: Discussionmentioning
confidence: 99%
“…The neutral red (NR) cytotoxicity assay was performed as described previously (Rowe et al, 2010). Cellular proliferation was evaluated by colorimetric MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay following the method developed by Mosmann (Mosmann, T.1983).…”
Section: Methodsmentioning
confidence: 99%
“…Skin was divided into approximately 1-cm 2 pieces, cultured on NetWells (Corning, NY), and inoculated with VZV-BAC-Luc by scarification with a 27-gauge needle (Rowe et al, 2010; Taylor and Moffat, 2005). For bioluminescence imaging, skin explants were submerged in D-luciferin (300 μg/mL in PBS) for 1 hour before scanning in the IVIS® 50.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of the binding kinetics of VZV MCP and its mutants with 35B2 and related compounds identified in the SAR analysis will help us to see whether 35B2 interacts with a tertiary structural element conserved among herpesviruses. Further studies are also required to see whether such anti-MCP compounds are effective in assays that represent various aspects of VZV infections in vivo, such as T lymphocyte cultures, skin raft/organ cultures, and SCID-hu mouse models (25,28,35,46,51).…”
Section: Fig 4 Comparison Of Amino Acid Sequences Between Hsv-1 Vp5 (mentioning
confidence: 99%